2010
DOI: 10.1007/s11274-010-0324-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biological control by the yeast Torulaspora globosa against Colletotrichum sublineolum in sorghum

Abstract: The yeasts are microorganisms with great potential for biotechnological applications in diverse areas. The biological control of phytopathogens by yeasts has showed satisfactory results under laboratory conditions, and it has already produced commercial formulations. With this as focus, this work aims to perform in vitro and in vivo evaluations of the action of a Torulaspora globosa yeast strain (1S112), isolated from sugarcane rhizosphere, against the phytopathogenic mold Colletotrichum sublineolum, the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 54 publications
1
42
0
1
Order By: Relevance
“…Yeasts are unicellular fungi that can also be found in the rhizosphere of plants, but in smaller numbers compared to bacteria and filamentous fungi; however, little information is known about their function in this ecosystem. A wide variety of yeasts present characteristics that promote plant growth (Cloete et al, 2009;Limtong et al, 2014;Nutaratat et al, 2014) via the control of plant pathogens (El-Tarabily, 2004;El-Tarabily and Sivasithamparam, 2006;Korres et al, 2011;Rosa et al, 2010), the production of phytohormones (Nassar et al, 2005), the solubilization of phosphate (Hesham and Mohamed, 2011;Falih and Wainwright, 1995;Mirabal Alonso et al, 2008;Mundra et al, 2011), the oxidation and mineralization of nitrogen and sulfur compounds (Falih and Wainwright, 1995), the production of siderophores (Sansone et al, 2005) and the stimulation of root colonization by mycorrhizal fungi (Mirabal Alonso et al, 2008;Vassileva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts are unicellular fungi that can also be found in the rhizosphere of plants, but in smaller numbers compared to bacteria and filamentous fungi; however, little information is known about their function in this ecosystem. A wide variety of yeasts present characteristics that promote plant growth (Cloete et al, 2009;Limtong et al, 2014;Nutaratat et al, 2014) via the control of plant pathogens (El-Tarabily, 2004;El-Tarabily and Sivasithamparam, 2006;Korres et al, 2011;Rosa et al, 2010), the production of phytohormones (Nassar et al, 2005), the solubilization of phosphate (Hesham and Mohamed, 2011;Falih and Wainwright, 1995;Mirabal Alonso et al, 2008;Mundra et al, 2011), the oxidation and mineralization of nitrogen and sulfur compounds (Falih and Wainwright, 1995), the production of siderophores (Sansone et al, 2005) and the stimulation of root colonization by mycorrhizal fungi (Mirabal Alonso et al, 2008;Vassileva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Este mismo hongo fue posteriormente inhibido con cepas de Pichia anomala y Debaryomyces hansenii, aumentando el arsenal bioló-gico con potencial biocontrolador frente a este patógeno . Cepas de Issatcehnkia orientalis, Candida guilliermondii, P. ohmeri y Torulaspora globosa, entre otras, han sido reportadas para la inhibición exitosa de hongos fitopatógenos de importancia tales como Aspergillus cabonarius, A. niger, Penicillium expansum y Colletotrichum sublineolum en cultivos de uva, pera, manzana y sorgo, respectivamente (Bleve et al, 2006;Coelho et al, 2009;Rosa et al, 2010). En México, Hernán-altering cell walls, membranes, or vulnerable cell nuclei (Buzzini et al, 2007).…”
Section: Introductionunclassified
“…The fungus Botrytis cinerea, one of the most harmful pathogens in grape and strawberry crops, was inhibited using the partially purified of the strain Pichia membranifaciens CYC 1106 . This same fungus was later inhibited using strains of Pichia anomala and Debaryomyces hansenii, increasing the biological arsenal with biocontrolling potential over this pathogen (Bleve et al, 2006;Coelho et al, 2009;Rosa et al, 2010). In Mexico, Hernández-Montiel et al, (2011) reported a significant reduction of Geotrichum citri-aurantii in limes during postharvest, using epiphytic D. hansenii yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Biocontrol strategies based on K yeasts were also proposed for ethanol production (Ceccato-Antonini et al 2004;Meneghin et al 2010) and in the food industry (Izgü et al 1997;Goretti et al 2009). The preservation of stored fruits from postharvest diseases (Pimenta et al 2008), and the protection of cheese (Liu and Tsao 2009) or cereals (Kitamoto et al 1999;Olstorpe et al 2010;Rosa et al 2010) against spoilage fungi and/or bacteria can also be achieved by exploring the killer phenomenon. Strategies of preservation based on biological control solutions offer an interesting alternative to the frequently used chemical preservatives, which are leading to resistance phenomena and face increased consumer resistance due to environmental concerns.…”
Section: Introductionmentioning
confidence: 99%